Multidimensional Engineering of Escherichia coli for Efficient Adipic Acid Synthesis From Cyclohexane - Fei Wang; Huiqi Sun; Di Deng; Yuanqing Wu; Jing Zhao; Qian Li; Aitao Li (Advanced Science)
Abstract Adipic acid (AA), a key aliphatic dicarboxylic acid, is conventionally manufactured through energy‐intensive, multi‐step chemical processes with significant environmental impacts. In contrast, biological production methods offer more sustainable alternatives but are often limited by low productivity. To overcome these challenges, this study reports the engineering of a single Escherichia coli for efficient biosynthesis of AA starting from cyclohexanol (CHOL), KA oil (mixture of CHOL and cyclohexanone (CHONE)), or cyclohexane (CH). To start with, a comprehensive screening of rate‐limiting enzymes is conducted, particularly focusing on cytochrome P450 monooxygenase, followed by the optimization of protein expression using strategies such as protein fusion, promoter replacement, and genome editing. Consequently, an engineered E. coli capable of efficiently converting either KA oil or CH into AA is obtained, achieving remarkable product titers of 110 and 22.6 g L−1, respectively. This represents the highest productivity record for the biological production of AA to date. Finally, this developed biocatalytic system is successfully employed to convert different cycloalkanes and cycloalkanols with varied carbon chain lengths into their corresponding dicarboxylic acids, highlighting its great potential as well as broad applicability for industrial applications.